Brain White Matter Development Over the First 13 Years in Very Preterm and Typically Developing Children Based on the T1-w/T2-w Ratio. (1st March 2022) - Thompson, Deanne K.; Yang, Joseph Y. M.; Chen, Jian; Kelly, Claire E.; Adamson, Christopher L.; Alexander, Bonnie; Gilchrist, Courtney; Matthews, Lillian G.; Lee, Katherine J.; Hunt, Rodney W.; Cheong, Jeanie L. Y.; Spencer-Smith, Megan; et al.
Abstract : Background and Objectives: To investigate brain regional white matter development in full-term (FT) and very preterm (VP) children at term equivalent and 7 and 13 years of age based on the ratio of T 1 - and T 2 -weighted MRI ( T 1 -w/ T 2 -w), including (1) whether longitudinal changes differ between birth groups or sexes, (2) associations with perinatal risk factors in VP children, and (3) relationships with neurodevelopmental outcomes at 13 years. Methods: Prospective longitudinal cohort study of VP (born <30 weeks' gestation or <1, 250 g) and FT infants born between 2001 and 2004 and followed up at term equivalent and 7 and 13 years of age, including MRI studies and neurodevelopmental assessments. T 1 -w/ T 2 -w images were parcellated into 48 white matter regions of interest. Results: Of 224 VP participants and 76 FT participants, 197 VP and 55 FT participants had useable T 1 -w/ T 2 -w data from at least one timepoint. T 1 -w/ T 2 -w values increased between term equivalent and 13 years of age, with little evidence that longitudinal changes varied between birth groups or sexes. VP birth, neonatal brain abnormalities, being small for gestational age, and postnatal infection were associated with reduced regional T 1 -w/ T 2 -w values in childhood and adolescence. Increased T 1 -w/ T 2 -w values across the white matter at 13 years were associated with better motor and working memory function for all children. Within the FT group only, larger increases in T 1 -w/ T 2 -w values from term equivalent to 7 years were associated with poorer attention and executive function, and higher T 1 -w/ T 2 -w values at 7 years were associated with poorer mathematics performance. Discussion: VP birth and multiple known perinatal risk factors are associated with long-term reductions in the T 1 -w/ T 2 -w ratio in white matter regions in childhood and adolescence, which may relate to alterations in microstructure and myelin content. Increased T 1 -w/ T 2 -w ratio at 13 years appeared to be associated with better motor and working memory function and there appeared to be developmental differences between VP and FT children in the associations for attention, executive functioning, and mathematics performance.